(untitled) - Kološtová, Mariana (Aura musica, 2019)
The article emphasizes 15 years of activity of the Slovak Society for Music Education which action in the continuity of the development of Slovak musical pedagogy has not been socially or historically appreciated yet. This article focuses on the diverse activities of the Society in the national context through the work of Viliam Fedor and Tibor Sedlický.
Keywords: Slovak Society for Music Education (SSHV); Viliam Fedor; Tibor Sedlický; contribution; branche offices; commissions; scientific and editorial activity